Growth and development, health and nutrition in southeast of South America - Oyhenart, Evelia Edith (2019)
In this paper, the history and current situation of studies on child growth and development, one of the main thematic units of biological anthropology in the South American countries Argentina, Bolivia, Chile, Paraguay and Uruguay, are described. Nevertheless, there is a lack of studies done on this subject in the region. This is the case of Paraguay and Uruguay and, to a lesser extent of Bolivia and Chile. Argentina shows a significant development. The analysis of the information gathered suggests that the process of growth and development recognizes a complex weave of socio-economic and socio-environmental factors influencing biological conditions such as nutritional status and health of populations. According to the complexity mentioned we can conclude that the epistemological strategy of the discipline, with future projection, lies on the promotion of interdisciplinary and multi-national and regional studies.